2018
DOI: 10.3775/jie.97.231
|View full text |Cite
|
Sign up to set email alerts
|

Production Test of Torrefied Woody Biomass Solid Fuel in an Original Small-scale Plant

Abstract: In this study, an original small-scale demonstration plant was manufactured to produce upgraded wood fuel by torrefaction. The plant consists of a rotary-kiln type oven and a ring-die type pelletizer, and they were optimized for torrefaction based on the commercial models. We succeeded in more than 240 h operation of the torrefaction oven and produced 2.3 t of torrefied chips from raw Japanese cedar chips without drying. The energy yield of the torrefied chips was more than double the energy yield of conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…After mixing the ground torrefied wood powder (obtained from the hammer mill) with starch, pelletization was conducted under the same conditions that were described in a previous study 3) . The mixing ratio of the additive was determined to be 2 wt.%, according to ISO 17225-2 4) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After mixing the ground torrefied wood powder (obtained from the hammer mill) with starch, pelletization was conducted under the same conditions that were described in a previous study 3) . The mixing ratio of the additive was determined to be 2 wt.%, according to ISO 17225-2 4) .…”
Section: Methodsmentioning
confidence: 99%
“…TC: Thermocouple. The location of the thermocouple was explained in a previous study 3) 1 is based on the test conditions of the previous study 3) , assuming that that the raw materials were purchased for JPY 8/kg-wet. It is also assumed that the total number of laborers required is ten (six personnel for the operation of the torrefaction oven and the remaining four for the operation of the pelletizer).…”
Section: Image For Commercial Plantmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to use on small scales, Yoshida et al studied the effects of torrefaction treatment conditions, mass yields, and calorific values at a laboratory scale [5,6]. They then constructed a demonstration plant with a treatment amount of 20 kg/h to continuously produce torrefaction chips from raw wood chips [7,8]. As a result of burning trials for the torrefied pellets in a commercial pellet stove, we found that the torrefied pellets demonstrated faster ignition time than normal pellets.…”
Section: Introductionmentioning
confidence: 99%